Correlations for flow boiling heat transfer in minichannels with various orientations. (February 2015) - Piasecka, Magdalena
Abstract: The paper presents the results of using known correlations for boiling heat transfer in a minichannel 1 mm deep, 40 mm wide and 360 mm long, with three spatial orientations: vertical, position 90° and two horizontal orientations: positions 0° and 180°. The heating element for cooling liquid flowing laminarly in the minichannel is a single-sided microstructured foil. Liquid crystal thermography was used for measuring the temperature distribution on the plain side of the heating surface. The observations of the flow structures were carried out on the microstructured side of the foil contacting fluid in the minichannel. 12 selected correlations for boiling heat transfer have been used in calculations. It was found that the majority of correlations enabled the predicting of heat transfer coefficient within an acceptable error limit (±30%) only in a specific orientation of the channel. For the horizontal channel, position 0°, the highest compliance occurred when Mikielewicz et al. correlation was applied, for the vertical channel – when Liu and Winterton correlation was used and for horizontal channel, position 180° – by the application of Cooper correlation. The own correlation, with taken account for the microstructured heating wall, was proposed in two forms: for saturated boiling and for boiling incipience and subcooled boiling. Most experimental data show congruence with theoretical correlations with the tolerance ±35%.